Hubungan Lama Hemodialisis Dan Tingkat Stres Dengan Kualitas Hidup Pasien Hemodialisa - Puspita Putri, Maharani; Ikhlasul Amal, Ahmad; Melastuti, Erna; Dwi Retno Sulistyaningsih (STIKes Ibnu Sina Ajibarang, 2025)
Hemodialysis is a treatment for chronic kidney disease patients using a specially designed device to filter and remove metabolic waste as a substitute for kidney function. Patients often experience complications or common psychological effects, such as stress and the duration of hemodialysis, which influence their quality of life. This study adopts a kuantitative approach with a cross-sectional technique. Data were obtained through the distribution of questionnaires to 99 participants. The entire population was used as a sample (total sampling), and the data were statistically processed using gamma testing. The research findings revealed that the duration of undergoing hemodialysis and stress levels have a significant impact on the quality of life of hemodialysis patients, with a significance value of p < 0.001 and correlation coefficients of 0.711 and -0.954, respectively.